k-30=k-63

Simple and best practice solution for k-30=k-63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-30=k-63 equation:



k-30=k-63
We move all terms to the left:
k-30-(k-63)=0
We get rid of parentheses
k-k+63-30=0
We add all the numbers together, and all the variables
33!=0
There is no solution for this equation

See similar equations:

| k+81=4k | | 7h+17=73 | | (11)(x)=0 | | d/9=13 | | x-36=6x | | (x+11)(x–10)=0 | | 3s-4.75=21 | | (6)(p)=54 | | m+12=8m | | g−62=14 | | n+30=28 | | r-6=2r | | V=3.14x18^2x8 | | 7.2y=18.3 | | 13x^2=90 | | (5x)+(2x)=90 | | -2a-5=3(5-2a) | | 3k+38=92 | | (60)+(4x)=90 | | 13–8x=141 | | 3(-2x+4)=-6x-12* | | 20=48t^2 | | 3s+4.75=21 | | 93/4−2s=21/4 | | x=74x≥13 | | 5=-1-7/k | | (4x+9)(5x+5)=180 | | 3(x+4)=-3* | | x^2-14x=287 | | 9x=135* | | 10(s-9)=-172 | | c/5c+5=30 |

Equations solver categories